2021
DOI: 10.1186/s40364-021-00283-y
|View full text |Cite
|
Sign up to set email alerts
|

Empiric use of anticoagulation in hospitalized patients with COVID-19: a propensity score-matched study of risks and benefits

Abstract: Background Hospitalized patients with COVID-19 demonstrate a higher risk of developing thromboembolism. Anticoagulation (AC) has been proposed for high-risk patients, even without confirmed thromboembolism. However, benefits and risks of AC are not well assessed due to insufficient clinical data. We performed a retrospective analysis of outcomes from AC in a large population of COVID-19 patients. Methods We retrospectively reviewed 1189 patients ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Indeed, the stratifications of VTE risk may increase the benefit–risk ratio of primary prevention of thrombosis using intermediate or therapeutic anticoagulant dose. This concept is supported by a retrospective monocentric study including critically ill COVID-19 patients, suggesting that this subgroup of patients with elevated D-dimer levels requiring mechanical ventilation—two risk factors identified in the present meta-analysis—may benefit from therapeutic anticoagulation [ 43 ]. Although subgroup analysis from recent trials did not show any interaction between D-dimer levels and the efficacy of full-dose anticoagulation, critically ill COVID-19 patients are likely to represent a highly heterogeneous group of patients with a diverse risk of VTE and bleeding.…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, the stratifications of VTE risk may increase the benefit–risk ratio of primary prevention of thrombosis using intermediate or therapeutic anticoagulant dose. This concept is supported by a retrospective monocentric study including critically ill COVID-19 patients, suggesting that this subgroup of patients with elevated D-dimer levels requiring mechanical ventilation—two risk factors identified in the present meta-analysis—may benefit from therapeutic anticoagulation [ 43 ]. Although subgroup analysis from recent trials did not show any interaction between D-dimer levels and the efficacy of full-dose anticoagulation, critically ill COVID-19 patients are likely to represent a highly heterogeneous group of patients with a diverse risk of VTE and bleeding.…”
Section: Discussionmentioning
confidence: 69%
“…Eight of the 11 RCTs compared therapeutic versus prophylactic doses of anticoagulants, and three trials compared moderate therapeutic versus prophylactic doses of anticoagulants. Seven of the 17 OBs trials involved critically ill patients [ 29 , 31 33 , 36 , 41 , 42 ], and ten involved non-critically ill patients [ 8 , 28 , 30 , 34 , 35 , 37 40 , 43 ]. The outcomes of the 28 clinical studies are summarized in Tables 3 and 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the forty-two included studies, 6 studies [ 34 – 39 ] were RCTs and 36 studies [ 40 75 ] were cohort studies. Thirteen studies [ 34 , 38 , 39 , 41 , 43 , 52 , 55 , 58 , 61 , 64 , 67 , 69 , 70 ] were performed exclusively in patients admitted to ICU.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Thirteen studies [ 34 , 38 , 39 , 41 , 43 , 52 , 55 , 58 , 61 , 64 , 67 , 69 , 70 ] were performed exclusively in patients admitted to ICU. Eighteen studies [ 34 , 40 , 42 , 48 , 51 , 53 – 55 , 57 , 62 66 , 68 70 , 73 ] reported results from the United States and two [ 37 , 38 ] were international studies. Other studies originated from eleven countries ( Italy [ 47 , 49 , 56 , 58 , 60 , 72 , 75 ], France [ 41 , 61 , 67 ], Brazil [ 35 , 36 ], England [ 59 ], Greek [ 46 ], China [ 45 ], Japan [ 43 ], Mexico [ 44 ], United Arab Emirates [ 52 , 71 ], Turkey [ 74 ], Iran [ 39 ] and Spain [ 50 ] ).…”
Section: Study Characteristicsmentioning
confidence: 99%